PP52 Interim Decision-Making To Address Uncertainty At Early Assessment. (2019) - Downes, Noreen; Jones, Jan; Lee, Anne; McGuire, Pauline
Abstract : Introduction: Medicines regulation has become increasingly adaptive to support earlier patient access but the immature clinical data is often challenging for health technology assessment decision-makers due to high levels of uncertainty on long term risks and benefits. Scottish Medicines Consortium (SMC) is therefore exploring new, more adaptive approaches to help manage this challenge. Methods: SMC consulted with key stakeholders including clinicians, the pharmaceutical industry and patient groups on a number of options that would allow the committee to make an interim decision that would be revisited based on later evidence. The ability to collect robust patient level data given data capabilities in National Health Service Scotland (NHSScotland) was an important consideration. Results: To ensure that additional evidence would be available to inform a re-assessment, the new approach applies to medicines with a Conditional Marketing Authorisation (MA) from the European Medicines Agency (EMA). This obligates the company to provide specified clinical data to the regulator within a pre-set timeframe. For these medicines, the SMC decision-making committee can accept or not recommend the medicine as at present but can also accept the medicine on an interim basis, if the regulator's mandated Specific Obligations are likely to address the uncertainties in the clinical evidence. When the regulator converts the MA from conditional to standard, the company is required to make a further SMC submission to allow a reassessment and a final decision. The company can also provide additional supplementary post-licensing patient level evidence at reassessment. Conclusions: This new decision option allows SMC to test an approach to managing uncertainty targeted at a small number of promising new medicines where there is unmet patient need, with the reassurance that a final decision will be supported by additional clinical data.